2021
DOI: 10.1111/ijcp.14684
|View full text |Cite
|
Sign up to set email alerts
|

Investigating tinnitus subgroups based on hearing‐related difficulties

Abstract: Purpose: Meaningfully grouping individuals with tinnitus who share a common characteristics (ie, subgrouping, phenotyping) may help tailor interventions to certain tinnitus subgroups and hence reduce outcome variability. The purpose of this study was to test if the presence of tinnitus subgroups are discernible based on hearingrelated comorbidities, and to identify predictors of tinnitus severity for each subgroup identified.Methods: An exploratory cross-sectional study was used. The study was nested within an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“… 7 In an extensive online survey of 3400 participants, tinnitus severity was highest in patients with a co-occurrence of tinnitus and hyperacusis. 8 Tinnitus patients who have recovered completely over time have reported lower fear-related hyperacusis. 7 …”
Section: Introductionmentioning
confidence: 99%
“… 7 In an extensive online survey of 3400 participants, tinnitus severity was highest in patients with a co-occurrence of tinnitus and hyperacusis. 8 Tinnitus patients who have recovered completely over time have reported lower fear-related hyperacusis. 7 …”
Section: Introductionmentioning
confidence: 99%
“…The participants in this current trial represented those with higher levels of education as the majority had a university degree, college, or vocational training. When subgrouping those with tinnitus, Beukes et al ( 56 ) suggested that the unique management pathways may be more suited for some tinnitus subgroups. Further work is required to identify which individuals with tinnitus are more suited for ICBT.…”
Section: Discussionmentioning
confidence: 99%
“…Tinnitus is a common condition and is experienced by 10-15% of the adult population, although only a small percentage (roughly 2%) are severely annoyed by this condition [1]. While various factors including pathophysiological aspects may contribute to the experience, it is still unclear why some people state that tinnitus does not interfere with everyday life whereas others find it extremely debilitating [2][3][4]. One possible explanation for this comes from the psychological model of tinnitus which suggests that cognitive factors play a crucial role in tinnitus experiences [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, that tinnitus should be viewed as a multidimensional symptom which can only be understood fully from the biopsychosocial perspective [6]. For these reasons, all theories including biological underpinnings, psychological mechanisms, as well as social aspects need to be examined to better understand the tinnitus experience [3,4,7].…”
Section: Introductionmentioning
confidence: 99%